INCIDENCE OF CYSTIC ECHINOCOCCOSIS IN CATTLE - Sangaran, A; John, Lalitha (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
In the present study an incidence of 11.57 per cent echinococcosis in cattle was found. Maximum percentage was observed in lungs followed by liver and lungs and liver both.